Characterization Of Populations Of Fusarium Oxysporum F. Sp. Cubense And Selection Of Somaclonal Variants Tolerant To Banana Wilt Desease - Goode, Simon Andrew (2005)

(untitled)
Sebanyak 40 isolat Fusarium oxysporum f. sp. cubense (FOC) dari Indonesia, Sumatra, dan Semenanjung Malaysia yang dipencil dan pelbagai variety pisang utama di Asia tenggara telah dikenalpasti dari segi morfologi, ras dan keserasian vegetatifnya. Keputusan analisis keserasian vegetatif (VCG) menunjukkan kehadiran 'clonal lineages' di Semenanjung Malaysia. Sebanyak 12 kelompok keserasian vegetatif telah dikenalpasti. Lima kelompok adalah sarna dengan VCG 0121, VCG 0124, VCG 01213, VCG 01216 dan VCG 01213/01216. Tujuh kelompok yang lain tidak dapat dikategorikan menggunakan sistem VCG yang sedia ada. Forty isolates of Fusarium oxysporum f. sp cubense (Foc) located in Indonesia (Sumatra) and Peninsular Malaysia were isolated from a diverse banana variety host range which included all significant South East Asian cultivars were characterized by morphology, race and vegetative compatibility (VCG). There appeared no direct pattern of association between race, VCG and morphological characteristics. VCG analysis indicated that there were several distinct clonal lineages present in Peninsular Malaysia. Twelve compatibility groups were identified, five of which were previously characterized as VCG 0121, VCG 0124, VCG 01213, VCG 01216 and VCG 01213/01216.